Role of Public Administration in Developing Countries: Examining the Role and Improvement of Public Administration in Developing Countries (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Public administration is an important aspect of the administration which exists in the political system and implement the policies which are formulated by the political executives. It does not only help in policy implementation but also in policy formulation. As far as developing countries are concerned, the role of public administration becomes more crucial because have to work for the overall development of every section of the society. The present paper highlights the role public administration in developing countries and effective suggestions to improve its working. This paper is totally based on secondary data and collected information from research papers, books, websites etc.